STUDI WATER BUS QUADRIMARAN PADA PERAIRAN DANGKAL - Muhammad Iqbal Rizwanto, (2022)
Modifying the number of hulls has been widely studied by varying the number of hulls to obtain an optimal hull. One way is to increase the number of hulls to be multihull. In this study, a comparison was made between the catamaran hull and the quadrimaran hull for variations in the ratio of shallow water. Hull modeling using maxsurf, and analysis of the effect of squat, sinkage trim by stern obtained using ANSYS AQWA Hydrodynamic Diffraction software. According to the simulation results on the effect of the squat, the quadrimaran hull has the most significant squat effect at an average of 14% lower than that of the catamaran hull. Meanwhile, in terms of the sinkage effect, the quadrimaran hull has the greatest sinkage effect with an average of 49% when trim by stern is smaller than the catamaran hull. And on the effect of trim, the LCG changes of -10% when trim by stern, on the catamaran and quadrimaran hulls produce the smallest sinkage effect. The effect of squat, sinkage, and trim, is very significant at the lowest depth condition, which is the H/T ratio = 1.2. It can be concluded that the quadrimara model issafer for sailing in shallow water areas than the catamaran model.